Duality of 5-HT Effects on Crayfish Motoneurons - Bacqué-Cazenave, Julien; Fossat, Pascal; Issa, Fadi A.; Edwards, Donald H.; Delbecque, Jean Paul; Cattaert, Daniel (Frontiers in Physiology, 2019)
Serotonin (5-HT) is a major neuromodulator acting on the nervous system. Its various effects have been studied in vertebrates, as well as in arthropods, from the cellular and subcellular compartments up to the behavioral level, which includes the control of mood, aggression, locomotion and anxiety. The diversity of responses of neurons to 5-HT has been related to its mode of application, the diversity of 5-HT-receptors, and the animals’ social status history. Among the various effects of 5-HT, the duality of 5-HT-evoked responses (excitatory / inhibitory) on motoneurons (MNs), sensorimotor pathways and their consequences on motor network activity has largely been studied in the locomotor network of isolated crayfish. The aim of the present report is to examine if this duality of exogenous 5-HT-evoked responses in the crayfish locomotor network can be reproduced by direct activation of 5HT neurons in the case of socially isolated animals. Our previous studies have focused on the mechanisms supporting these opposite effects on MNs, pointing out spatial segregation of 5-HT receptors responsible either for positive or negative responses. Here, we report new findings indicating that excitatory and inhibitory effects can be achieved simultaneously in different leg MNs by the activation of a single 5HT cell in the first abdominal ganglion.